Fundamentals of fluid mechanics - Munson, Bruce Roy 1940- (John Wiley & Sons, Inc., 1994)
Examines the fundamental aspects of fluid motion including important fluid properties, regimes of flow, pressure variations in fluids at rest and in motion, methods of flow description and analysis. Expands on basic analysis techniques used to solve fluid mechanics problems, stressing how flow phenomena are described mathematically and on when and how to use infinitesimal and finite control volumes. More than 160 examples are presented, providing detailed solutions to a variety of problems. Generous sets of homework problems in every chapter emphasize practical applications of principles. Changes in the new edition include a new chapter on turbomachinery as well as additional open-ended homework problems and expanded problems using experimental data.